2013
DOI: 10.1007/s10964-013-9968-7
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating Early Fatality: Friends’, Schoolmates’ and Individual Perceptions of Fatality on Adolescent Risk Behaviors

Abstract: Past research indicates that anticipating adverse outcomes, such as early death (fatalism), is associated positively with adolescents' likelihood of engaging in risky behaviors. Health researchers and criminologists have argued that fatalism influences present risk taking in part by informing individuals' motivation for delaying gratification for the promise of future benefits. While past findings highlight the association between the anticipation of early death and a number of developmental outcomes, no known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…These studies provide some evidence for the positive relationship between futurelessness and deviant behavior. Indeed, a handful of empirical studies have explored this link (Brezina et al, 2009; Clinkinbeard, 2014; Haynie, Soller, & Williams, 2014; Kruger et al, 2018; Piquero, Farrington, & Jennings, 2018; Wainwright, Nee, & Vrij, 2018). These studies have employed various operationalizations of futurelessness including the time discounting of money (Piquero et al, 2018), perceived age at death (Brezina et al, 2009; Clinkinbeard, 2014; Haynie et al, 2014; Piquero, 2016), hope for becoming who one wishes to be in the future (Wainwright et al, 2018), and having a present versus a future orientation (Kruger et al, 2018).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…These studies provide some evidence for the positive relationship between futurelessness and deviant behavior. Indeed, a handful of empirical studies have explored this link (Brezina et al, 2009; Clinkinbeard, 2014; Haynie, Soller, & Williams, 2014; Kruger et al, 2018; Piquero, Farrington, & Jennings, 2018; Wainwright, Nee, & Vrij, 2018). These studies have employed various operationalizations of futurelessness including the time discounting of money (Piquero et al, 2018), perceived age at death (Brezina et al, 2009; Clinkinbeard, 2014; Haynie et al, 2014; Piquero, 2016), hope for becoming who one wishes to be in the future (Wainwright et al, 2018), and having a present versus a future orientation (Kruger et al, 2018).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Indeed, a handful of empirical studies have explored this link (Brezina et al, 2009; Clinkinbeard, 2014; Haynie, Soller, & Williams, 2014; Kruger et al, 2018; Piquero, Farrington, & Jennings, 2018; Wainwright, Nee, & Vrij, 2018). These studies have employed various operationalizations of futurelessness including the time discounting of money (Piquero et al, 2018), perceived age at death (Brezina et al, 2009; Clinkinbeard, 2014; Haynie et al, 2014; Piquero, 2016), hope for becoming who one wishes to be in the future (Wainwright et al, 2018), and having a present versus a future orientation (Kruger et al, 2018). Most of these studies are correlational examining futurelessness and offending cross-sectionally (Brezina et al, 2009; Clinkinbeard, 2014; Kruger et al, 2018; Piquero, 2016; Piquero et al, 2018; Wainwright et al, 2018).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…These beliefs capture the extent to which people look ahead in their lives with more or less optimism (Peterson 2000), and predict beneficial life course outcomes, net of socioeconomic and demographic factors (Halleröd 2011; Hitlin and Johnson 2015). Related expectations about the future regarding schooling, as well as those about survival, are associated cross-sectionally with lower substance use and violent and nonviolent antisocial behavior (Brumley et al 2017; Haynie et al 2014) and longitudinally with reduced sexually risky and violent behavior (Brumley et al 2017; Sipsma et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Similar to other research, findings from this study report that friends have an influence on the type of behavior college Black men engage in. 42 Research has reported that fatalism, belief that you will die at a young age, of one’s friends had a positive effect on risky behaviors adolescents engaged in. 42 Findings from this study also reported that college Black males want role models their age who are engaged in healthy behaviors so that they can emulate them.…”
Section: Commentmentioning
confidence: 99%
“…42 Research has reported that fatalism, belief that you will die at a young age, of one’s friends had a positive effect on risky behaviors adolescents engaged in. 42 Findings from this study also reported that college Black males want role models their age who are engaged in healthy behaviors so that they can emulate them. This finding supports a larger concept that peer support, assistance given by non-professionals that includes emotional, social, and practical assistance to encourage healthy behaviors, may be a more effective way to engage hardly reached groups, based on individual, demographic, or cultural-environmental factors, and improve their health outcomes.…”
Section: Commentmentioning
confidence: 99%